Leveraging Artificial Intelligence-Supported Quizlet Flashcards to Enhance Arabic Vocabulary Acquisition among Madrasah Students - Nur'atika,; Nurlaila,; Sri Wahyuningsih, (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
Arabic vocabulary acquisition remains a major challenge for many learners, particularly in contexts where instruction is dominated by memorization and teacher-centered approaches. This study aimed to investigate the implementation of Artificial Intelligence-Supported Quizlet Flashcards in enhancing Arabic vocabulary acquisition among eleventh-grade students at MA Muhammadiyah Kota Bima. The study employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection stages conducted across two cycles. The participants were 12 students. Artificial Intelligence was utilized as a supporting tool for developing vocabulary materials, contextual example sentences, and learning exercises that were subsequently integrated into Quizlet flashcards. Data were collected through observation, tests, and documentation and analyzed using descriptive quantitative techniques. The findings revealed a consistent improvement in students’ vocabulary acquisition throughout the research cycles. The mean score increased from 67 in the pre-cycle stage to 75.17 in Cycle I and 80.67 in Cycle II. Similarly, the learning mastery rate improved from 16.7% in the pre-cycle stage to 50% in Cycle I and reached 83.33% in Cycle II. These findings indicate that AI-Supported Quizlet Flashcards can provide a more interactive, flexible, and engaging learning experience, thereby supporting students’ Arabic vocabulary acquisition. The study highlights the potential of integrating AI-assisted learning-material development with digital flashcard platforms to enhance Arabic language learning in madrasah settings.